Przeciwko autorytetowi tekstu I: „Opis obrazu" Heinera Mullera jako negacja teatralności tekstu - Sugiera, Małgorzata (Przestrzenie Teorii, 2008)
In Bildbeschreibung (Description of a Picture, 1984) Müller deliberately fails to match up with the basic tenets of the theatricality typical of a dramatic text. Simultaneously, however, he equally deliberately posits a challenge to the theatre and puts into question the dominant idea of the dramatic text and its stageability. The aim of this essay is to raise questions about the methods and principles of inscribing the author's intentions in the text and the possibility of recognizing the text's destination and stage potential. I attempt to answer these questions, reading Bildbeschreibung as a borderline case in the context of Strindberg's To Damascus and Brecht's Massnahme in order to point to the basic relationship between the texts written nowadays for the stage and the modern stage practice, since without addressing this issue it is impossible to lay grounds for a new methodology of text analysis and interpretation.